When reflex reactions oppose voluntary commands: The StartReact effect on eye opening - Valls-Solé, Josep; Castellote, Juan M; Kofler, Markus; Serranová, Tereza; Versace, Viviana; Campostrini, Stefania; Campolo, Michela (Psychophysiology, 2021)
A startling auditory stimulus (SAS) induces a reflex response involving, among other reactions, a strong contraction of the orbicularis oculi muscle (OOc) and subsequent eye closure. A SAS also induces the StartReact effect, a significant shortening of reaction time in subjects ready for task execution. We examined the obvious conflict appearing when a StartReact paradigm requires participants with eyes closed to open their eyes to look for a visual target. We recorded OOc EMG activity and eyelid movements in healthy volunteers who were instructed to open their eyes at perception of a somatosensory imperative stimulus (IS) and locate the position of a Libet's clock's hand shown on a computer screen at 80 cm distance. In 6 out of 20 trials, we delivered a SAS simultaneously with the IS. The main outcome measures were reaction time at onset of eyelid movement and the time gap (TG) separating subjective assessment of the clock's hand position from real IS issuing. Control experiments included reaction time to eye closing and target location with eyes open to the same IS. Reaction time was significantly faster in SAS than in noSAS trials and slower for eye opening than for eye closing in both conditions. In the eye-opening task, TG was significantly shorter in SAS with respect to noSAS trials, despite the presence of the SAS-related burst in the OOc before EMG cessation. Our results indicate that the StartReact effect speeds up eye opening and location of a target in the visual field despite the startle reaction opposing the task.
Keywords: úleková reakce; dospělí; Female; Facial Muscles; Psychomotor Performance; reakční čas; Adult; ženské pohlaví; mladý dospělý; oční víčka; Physical Stimulation; lidé; psychomotorický výkon; Auditory Perception; Visual Perception; sluchová percepce; Electromyography; zraková percepce; Male; Aged; Young Adult; Reaction Time; lidé středního věku; Reflex, Startle; senioři; obličejové svaly; mužské pohlaví; fyzikální stimulace; Middle Aged; Eyelids; elektromyografie; Humans